Influence of overgrowing terms and soil type on agrophysical indicators of different soil types located on the accumulative direction of the matter-energy flow - A. V. Lednev; A. V. Dmitriev (Аграрная наука Евро-Северо-Востока, 2017)
According to the materials of 2015 expeditionary soil approbation the key areas, located on the accumulative relief forms are revealed in the Udmurt Republic. Complex observations were taken in arable land, fallow land, and forest. It was found that soil type and period of arable land overgrowing have an impact on the direction and intensity change of agrophysical properties of soils at deriving them from agricultural use. Changes in agrophysical soil properties concerned only the upper part of the profile (arable layer and subsoil). It was shown that the overgrowing of agro-sod-podzolic soils in the taiga-forest zone leads inevitably to the differentiation of arable layer into two sublayers. Sod process of soil formation is putted on its upper part, which causes the reduction of soil density from 1.33 up to 1.15 g/cm3 and significant improvement in the structural state of this sublayer (structural coefficient has increased by 4-10 times). Zonal podzolic process begins to put in bottom part of arable layer and therefore structural coefficient remains at the same low level. The maximum degree of differentiation was observed in fallow with a very long period of overgrowing (20 years and over). According to these indicators fallow land had only little differences from its virgin counterpart. Agro-gray soils in contrast to agro-sod-podzolic characterized by a lower density of arable layer, had better soil pedality and not so sharp differentiation on sublayers on these indicators. The parameters of change in agrophysical soil properties depending on the term of overgrowing were revealed. Change in these parameters confirmed the possibility of division of time arable land overgrowing into three periods: the first period - up to 10 years; second - 10-20 years; third - more than 20 years.